PETA KEMANDIRIAN KEUANGAN DAERAH KABUPATEN DAN KOTA DI PROVINSI JAWA TENGAH - Soeharjoto Soekapdjo (Politeknik Negeri Batam, 2018)
Purpose of this study is to find out about financial independence map of the districts and cities in Central Java. Which using descriptive statistics, with IKF, DDD and KKD approaches. IKF approach still has intervention from the central government such as a budget assistance, while the DDD and KKD approaches just rely on on the ability of the region itself in the form of PAD. Results of financial independence map in Central Java Province with the IKF approach were obtained : 3 cities at medium category, 2 cities at low category and 1 city at very low category, while all of 29 districts were in the very low category. DDD and KKD obtained the same results, there is one city in “fair” category, three city at “moderate” category, and two cities at “minus” category, while for 23 districts are at minus category and one district at very minus category.